Abstraction : Towards a New Art Painting 1910-20. - Vergo, Peter; Green, Christopher; Beckett, Jane; Ades, Dawn (London : Tate Gallery, 1980)
Hoelzel, Adolf ; Itten, Johannes ; Larionov, Mikhail ; Goncharova, Nataliya ; Malevich, Kasimir ; Rodchenko, Alexander ; Popova, Lyubov ; Exter, Alexandra ; Burlyuk, Vladimir ; Lentulov, Aristarkh ; Boccioni, Umberto ; Severini, Gino ; Balla, Giacomo ; Magnelli, Alberto ; Lewis, Wyndham ; Wadsworth, Edward ; Dove, Arthur ; Hartley, Marsden ; O'Keeffe, Georgia ; Weber, Max ; Dreher, Katherine ; Davis, Stuart ; Stella, Joseph ; etc.
Abstraction: Towards a New Art Painting 1910-20, The Tate Gallery, London, 6 February - 13 April 1980
boek